Audio Engagement and Learning. Issue 4 (2nd October 2018) - Curran, Andy; Seo, Kay K.
ABSTRACT: Sound effects and music can be used to complement instructional narrations in recorded media presentations. College students ( n = 143) participated in a study examining the effects of music and sound effects on learning outcomes when compared to voice-only narration. Four groups of participants listened to a recorded short story and answered questions about the story. The control group's story was a voice-only narration. The three treatment groups' story was enhanced with one of the following: sound effects, music, or a combination of sound effects and music. Means for each group were not significantly different, and the difference of means between and within each of the groups was also found not to be significant. The results indicated that the presence of sound effects and music in an audio-only presentation did not significantly increase or decrease learning.